Sistem Pakar Kelayakan Perizinan pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Menggunakan Metode Forward Chaining - Nanang Susanto; Junadhi; Helda Yenni; M Jamaris (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
Efforts to increase investment in the regions need to be carried out with intensification and extensification activities, improving the implementation of excellent services through the formulation of strategic planning. Policies in the investment sector are basically aimed at increasing the ability of the regions to invite investors to enter the city of Medan. So far, the process of granting permission is by registering by filling out the form and uploading the required files, then the team will verify the files manually, this kind of work is considered less effective because it takes quite a long time. Likewise, the central government often changes regulations related to financial management, licensing, investment-related aspects, so that the regions must immediately adapt to the new regulations. The system process that uses the forward chaining method is by solving problems that are tracked based on existing facts until conformity is found based on the Rules that are formed until conclusions are found. The research that has been done can be concluded that the Expert System using the forward chaining method which is applied to the system in determining the feasibility of licensing is good enough to be applied because it can help the community, the investment office in determining the feasibility of the proposed business through the system. This expert system also provides information on recommendations for improvement to people who submit but are not yet eligible, so that they can easily adjust the conditions, facilities, and other supports to the standards made by the government.